New surface radiolabeling schemes of super paramagnetic iron oxide nanoparticles (SPIONs) for biodistribution studies1. Issue 15 (21st April 2015) - Nallathamby, Prakash D.; Mortensen, Ninell P.; Palko, Heather A.; Malfatti, Mike; Smith, Catherine; Sonnett, James; Doktycz, Mitchel J.; Gu, Baohua; Roeder, Ryan K.; Wang, Wei; Retterer, Scott T.
<x xml:space="preserve">Abstract</x> We present different surface radiolabeling schemes broadly applicable to a large class of nanoparticles, with wide implications for in vivo biodistribution studies.